Optimization of Manufacturing Processes - Gupta, Kapil; Gupta, Munish Kumar (Springer Series in Advanced Manufacturing, 2020)
This book provides a detailed understanding of optimization methods as they are implemented in a variety of manufacturing, fabrication and machining processes. It covers the implementation of statistical methods, multi-criteria decision making methods and evolutionary techniques for single and multi-objective optimization to improve quality, productivity, and sustainability in manufacturing. It reports on the theoretical aspects, special features, recent research and latest development in the field.